The impact of reinsurance indicators on the financial surplus of the National Insurance Company: applied research in marine insurance / merchandise branch (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research dealt with the impact of reinsurance on the financial surplus of the National Insurance Company by focusing on reinsurance in the marine insurance / merchandise branch. The aim of this research was to show the impact of reinsurance indicators (reinsurance ratios, retention ratios, commission rates earned) on reinsurance operations Data on the research variables were collected based on the inductive and deductive approach in the analysis of information for the financial reports of the National Insurance Company of the Marine Insurance Branch and the insurance portfolio (goods) for the period from 2010 to 2017, and for the purpose of obtaining results was used M a number of statistical methods commensurate with the nature of the data collected, as the use of Statistical Package for the Social Sciences Program (SPSS), in calculating the regression equation, test F, R2 coefficient selectionThe researcher reached a number of conclusions concerning the practical side, the most important (the results of statistical and financial analysis showed that there is a strong and significant impact relationship between the reinsurance indicators of the Marine Insurance / Merchandise Branch in the financial surplus, that the retention of insurance premiums within the state benefits the national economy it helps to reduce Financial flows issued outside the country in hard currencies in addition to providing financial surpluses and good savings for local investment, and based on the findings of the research has been presented a set of recommendations to the company in question, which is consistent with the reality of the research, the most important ( The need to reduce the reinsurance ratio issued by increasing the retention limits in the Marine / Cargo insurance branch, the need to review the marine. reinsurance agreements and focus on the loss-overriding agreements for the transfer of risks